Solar and geomagnetic activity effects on mid-latitude F-region electric fields - V. V. Kumar; M. L. Parkinson; P. L. Dyson; R. Polglase (Annales Geophysicae, 2008)
Diurnal patterns of average F-region ionospheric drift (electric field) and their dependence on solar and geomagnetic activity have been defined using digital ionosonde Doppler measurements recorded at a southern mid-latitude station (Bundoora 145.1° E, 37.7° S geographic, 49° S magnetic). A unique database consisting of 300 907 drift velocities was compiled, mostly using one specific mode of operation throughout 1632 days of a 5-year interval (1999–2003). The velocity magnitudes were generally larger during the night than day, except during the winter months (June–August), when daytime velocities were enhanced. Of all years, the largest drifts tended to occur during the high speed solar wind streams of 2003. Diurnal patterns in the average quiet time (AE<75 nT) meridional drifts (zonal electric field) peaked at up to ~6 m s−1 poleward (0.3 mV m−1 eastward) at 03:30 LST, reversing in direction at ~08:30 LST, and gradually reaching ~10 m s−1 equatorward at ~13:30 LST. The quiet time zonal drifts (meridional electric fields) displayed a clear diurnal pattern with peak eastward flows of ~10 m s−1 (0.52 mV m−1 equatorward) at 09:30 LST and peak westward flows around midnight of ~18 m s−1 (0.95 mV m−1 poleward). As the AE index increased, the westward drifts increased in amplitude and they extended over a greater fraction of the day. The perturbation drifts changed in a similar way with decreasing Dst except the daytime equatorward flows strengthened with increasing AE index, whereas they became weak for Dst<−60 nT. The responses in all velocity components to changing solar flux values were small, but net poleward perturbations during the day were associated with large solar flux values (>192×10−22 W m−2 Hz−1). These results help to more fully quantify the response of the mid-latitude ionosphere to changing solar and geomagnetic conditions, as required to refine empirical and theoretical models of mid-latitude electric fields.